Competitive Strategies in Thailand’s Swiftlet House Business: A Conceptual Framework for Entrepreneurial Adaptation and Financial Management - Ratanakitkoson, Areerat; Chaiyasoonthorn, Wornchanok; Chaveesuk, Singha (My University, 2026)
Thailand’s swiftlet house industry is a high-value sector with significant export potential and has attracted considerable international research attention. By contrast, domestic scholarship remains limited, with most studies focusing separately on technology, marketing, or finance, lacking an integrated approach to explain how these dimensions collectively influence competitive performance. This study aims to develop an integrated conceptual framework that explains the relationship between entrepreneurial adaptation (EA), covering technology, consumer behavior, and business networks and financial management (FM), including fixed cost management, variable cost management, and asset management. Together, these factors influence competitive strategies (CS) in terms of product quality, timing, pricing, and channel expansion. The research adopts a systematic literature synthesis, integrating the Resource-Based View (RBV) and Dynamic Capabilities Theory (DCT) to clarify the interconnections among these key variables. The developed framework can be applied to guide entrepreneurs in strategic planning and resource management, as well as support relevant agencies in policy formulation to enhance industry.
Keywords: Competitive strategies; Entrepreneurial adaptation; Financial management; Swiftlet house business